Effect of Anodization Voltage on TiO2 Nanotubes for Photodegradation of Formaldehyde - Sahrin, N.T. (Springer Science and Business Media B.V., 2021)
In this work, titanium dioxide nanotubes (TiO2 NTs) were prepared via electrochemical anodization of titanium foil in choline chloride-glycerol ionic liquid as the electrolyte. The anodization voltage was varied from 5 to 50Â V to investigate its effect on the properties of TiO2 NTs. The NTs were characterized using FESEM and XRD analyses while the photocatalytic performance of the NTs was investigated for photodegradation of formaldehyde (HCHO) under visible light irradiation. Experimental results showed that the anodization voltage has an important impact on the surface morphology of TiO2 NTs and the amorphous phase without heat treatment process. Higher anodization voltage led to pore rupture. TiO2 NTs fabricated at anodization voltage of 30Â V showed enhanced photocatalytic performance where 26.99Â mgÂ Lâ1Â gâ1 of removal after 120Â min of reaction duration in the presence of visible light radiation. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.